A Comparative Assessment of Outcomes of Skin Only Versus Deep Plane Brow Lift - Kamal Uddin Khan, Farzana Abdullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Facial aging is often visible in the way the eyebrows begin to move downward. When you are young, your eyebrows typically arch from side to side and sit either at or just above the supraorbital ridge. When the upper eyelid becomes laterally hooded, together with crow’s feet, the face appears fatigued or angry. Materials and Methods: A randomized controlled trial was conducted from June 2022 to January 2023 in which patients with age range of 40 to 65 years with weak brows and upper eyelid hooding were recruited. While those patients who had previous history of ocular procedures, neuromuscular disorders, and having previous forehead surgeries were excluded from the study. Results: Patients’ ages were approximately 52 years in both groups and most were female (60%). Preoperatively, the mean height of the brow was very close to being identical on both sides, regardless of its lateral tail or mid-brow section (lateral tail ~ 12.3 mm, mid-brow ~14.8 mm above reference line, p>0.5). After dichotomization, 94% of patients having deep-plane surgery were happy or very happy (scores 4–5), as opposed to 88% in the skin-only group. Conclusion: When compared, deep plane brow lifting achieved greater brow lift and patient satisfaction at 1-year follow-up in those of South Asian descent, outperforming skin-only brow lifting. Satisfaction with the result was very high for everyone, but the deep plane group experienced larger improvements in lateral and central brow lift. Keywords: Browlift, Eyelid, Eyebrows, Ocular Procedure.